PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 8 PEKANBARU - Sulastri, Mira; Munjiatun, Munjiatun; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research carried out base on the lowly of the result of mathematic in grade II SD Negeri 8 Pekanbaru which is about 70,7 from 34 students within minimal completeness criterion (KKM) stated is 75. This research is classroom action research (CAR). The purpose of this research is to improve mathematic learning process of class II SD Negeri 8 Pekanbaru in academic year 2014/2015 through Quantum Teaching. The research was conducted into 2 cycles. Each cycle consist of two meeting and one test. The instrument used in this study is the teacher and student’s activity sheet as well as learning about the test result. This study presents an increase of average teacher’s activity in the first cycle in first meeting is 67,3%, the second meeting increase to 78,8%. The second cycle increase from 82,6% to 96,1%. Student activity based on the result of research on first cycle is from 58,3% in the first meeting to 70,8% in the second meeting. In the second cycle increase from 89.5% in the first meeting to 95,8% in the second meeting. Based on the research of students learning outcome increased from the base score 70,7 to 83,3 in the first cycle and the second cycle increase become 92,7. Based on the result of the research, it can be concluded that the implementation of Quantum Teaching can improve the student’s achievement in mathematic subject of class II SD Negeri 8 Pekanbaru.Key words: Quantum Teaching, Student’s Mathematic Achievement